WIND-POWERED AGRICULTURE: ENHANCING CROP PRODUCTION AND ECONOMIC PROSPERITY IN ARID REGIONS - Usman, Habib Muhammmad; Mahmud, Muhammad; Yahaya, Madaniyyu Sulaiman; Saminu, Sani (Elektrika, 2024)
Over an extended duration, small-scale farmers have been contending with the persistent issue of electricity scarcity, which adversely affects crop production, particularly during dry seasons. The dependence on generators, despite being expensive and environmentally harmful due to oil spillage and Carbon dioxide (CO2) emissions, remains a prevalent yet unsustainable solution. Wind energy emerges as a promising alternative with diverse benefits for farmers, addressing concerns related to irrigation, storage, and water management, ultimately leading to significant yield increases during dry periods. This study investigates the performance of a small-scale wind energy conversion system tailored for the irrigation needs of farmers in arid regions, focusing on Zaria Local Government, Kaduna State, Nigeria as a case study. Utilizing wind speed data from the Nigeria Meteorological Agency (NIMET), the system's electrical parameters, including voltage, current, frequency, and power, were analyzed to assess fluctuations resulting from wind speed variations. Results show significant variability in electrical parameters: wind speed ranged from 3.10 m/s to 9.83 m/s, resulting in fluctuations in generated voltage (98 volts to 250 volts), current (51 amps to 103 amps), frequency (39 Hz to 65 Hz), and power (5.1 kW to 20.6 kW). Converter systems were found effective in stabilizing output for grid integration: the AC/DC converter converted fluctuating AC signals into stable DC output (200 volts, 93 amps), while the subsequent DC/AC inverter produced non-fluctuating AC output (voltage: 200 volts, current: 92 amps, frequency: 50 Hz, power: 18.3 kW). These findings emphasize feasibility of implementing wind energy solutions in remote agricultural areas.